Creative pedagogy as an innovative industry and the condition of formation of creativity trainee - Diana Aleksandrovna Khokhlova (Наука. Инновации. Технологии, 2022)
The article says about the place and value of creative pedagogy in the system of human Sciences and educational practice; as well as the pedagogical conditions of realization of the creative orientation of education of the individual in a continuous educational process